The impact of climate change on economic growth: A study of ASEAN countries - Phan , Thi Hang Nga; Pham, Cong Tien; Nguyen, Quoc Cuong (Journal of Finance - Marketing Research, 2024)
Climate change is an urgent and worldwide concern that presents substantial risks to a range of industries, such as agriculture, water resources, and economic growth. The purpose of this research is to assess how climate change has affected the economic expansion of ASEAN nations. Land pollution, sea level rise, and carbon dioxide (CO2) emissions are utilized to quantify climate change. Empirically investigating this issue, the Fixed Effects Generalized Least Squares (FGLS) method is utilized in conjunction with panel data spanning the years 1990 to 2018. The findings from the FGLS model estimation suggest that climate change exerts a varied influence on the economic growth of ASEAN member states. More precisely, total pesticide use in agriculture has a positive impact on economic development, whereas CO2 emissions have a detrimental effect. Moreover, economic growth is positively impacted by foreign direct investment, trade openness, and institutional stability. To stimulate economic expansion and bolster growth drivers, ASEAN nations must adopt more robust measures to deal with climate change.